Hypertrophic Stimulation Increases β-actin Dynamics in Adult Feline Cardiomyocytes - Balasubramanian, Sundaravadivel (Public Library of Science, 2010)
The myocardium responds to hemodynamic stress through cellular growth and organ hypertrophy. The impact of cytoskeletal elements on this process, however, is not fully understood. While α-actin in cardiomyocytes governs muscle contraction in combination with the myosin motor, the exact role of β-actin has not been established. We hypothesized that in adult cardiomyocytes, as in non-myocytes, β-actin can facilitate cytoskeletal rearrangement within cytoskeletal structures such as Z-discs. Using a feline right ventricular pressure overload (RVPO) model, we measured the level and distribution of β-actin in normal and pressure overloaded myocardium. Resulting data demonstrated enriched levels of β-actin and enhanced translocation to the Triton-insoluble cytoskeletal and membrane skeletal complexes. In addition, RVPO in vivo and in vitro hypertrophic stimulation with endothelin (ET) or insulin in isolated adult cardiomyocytes enhanced the content of polymerized fraction (F-actin) of β-actin. To determine the localization and dynamics of β-actin, we adenovirally expressed GFP-tagged β-actin in isolated adult cardiomyocytes. The ectopically expressed β-actin-GFP localized to the Z-discs, costameres, and cell termini. Fluorescence recovery after photobleaching (FRAP) measurements of β-actin dynamics revealed that β-actin at the Z-discs is constantly being exchanged with β-actin from cytoplasmic pools and that this exchange is faster upon hypertrophic stimulation with ET or insulin. In addition, in electrically stimulated isolated adult cardiomyocytes, while β-actin overexpression improved cardiomyocyte contractility, immunoneutralization of β-actin resulted in a reduced contractility suggesting that β-actin could be important for the contractile function of adult cardiomyocytes. These studies demonstrate the presence and dynamics of β-actin in the adult cardiomyocyte and reinforce its usefulness in measuring cardiac cytoskeletal rearrangement during hypertrophic stimulation.